The silver swamp - Charman, Katrina; Tondora, Judit (New York : Branches/Scholastic Inc., 2020)
When Blaze is captured by giant birds, Tag and Skyla search the Cloud Kingdom for her, including the dangerous Silver Swamp, with only their magical map as a guide.
Ages 6-8.
Grades 2-3.
590L
Decoding demand: 70 (high) Semantic demand: 93 (very high) Syntactic demand: 71 (high) Structure demand: 84 (very high)
Keywords: Owls -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Magic -- Juvenile fiction; Action and adventure fiction; Fantasy fiction